Desain Sistem Peringatan Dini Bencana Kebakaran Hutan Berbasis Jaringan Sensor dan Short Message Service (SMS) - Muhamad Iradat Achmad; Muhamad Iqbal Achmad (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2023)
Forest fires in a number of areas in Indonesia have become more frequent in recent years. This incident raises many problems in various areas of life. The Indonesian government has and continues to make preventive and curative efforts to minimize the occurrence of forest fires and the losses that occur. In line with the government's efforts, this paper proposes the design of a forest fire early warning system based on a sensor network and Short Message Service (SMS). This system consists of a subsystem on the forest side and a subsystem on the observation office side. The subsystem in the forest uses a sensor network of fire detector modules, smoke of MQ2, temperature and humidity of DHT11 to read the state of the forest, and utilizes the microcontroller of ATmega16 to acquire and process forest state data. Data processing that produces indications of forest fires will trigger the sound of sirens to convey these indications quickly to the people living around the forest. The data is sent to the observation office subsystem via SMS packets of GSM network. The monitoring application receives data of forest conditions and stores them in a database for further data processing.